2022
DOI: 10.1007/jhep01(2022)164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fully coherent energy loss on heavy meson production in pA collisions

Abstract: Hadron production in proton-nucleus (pA) collisions was previously shown to be suppressed by medium-induced fully coherent energy loss (FCEL). We show that the quenching of D and B mesons in pPb collisions at the LHC due solely to FCEL is, at least, on par with other nuclear effects such as gluon shadowing or saturation. This is consistent with previous findings for both quarkonium and light hadron production in pA collisions, emphasising that FCEL effects need to be included for a reliable understanding of ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…It has been demonstrated that the FCEL effects on D and B production is quite relevant and similar to those quantified in quarkonium and light hadron production. It is argued that the effect corresponds to about half of the nuclear suppression measured at the LHC at forward rapidities and low P T [76]. After inspection, our results at midrapidity are compatible with those studies.…”
Section: Gs (Approx)supporting
confidence: 91%
See 1 more Smart Citation
“…It has been demonstrated that the FCEL effects on D and B production is quite relevant and similar to those quantified in quarkonium and light hadron production. It is argued that the effect corresponds to about half of the nuclear suppression measured at the LHC at forward rapidities and low P T [76]. After inspection, our results at midrapidity are compatible with those studies.…”
Section: Gs (Approx)supporting
confidence: 91%
“…the fully coherent energy loss (FCEL) in cold nuclear matter on the open heavy-flavour production has been investigated in Ref. [76]. It has been demonstrated that the FCEL effects on D and B production is quite relevant and similar to those quantified in quarkonium and light hadron production.…”
Section: Gs (Approx)mentioning
confidence: 99%
“…4, where 10 panels report the results in different 𝑦 * subintervals. The results are compared with several theoretical calculations: reweighted EPPS16 [8] and nCTEQ15 [9] nPDF sets calculated with HELAC-Onia approach [6,7], two calculations based on the CGC effective field theory [10][11][12] and a calculation estimates 𝐷 0 suppression caused by medium-induced fully coherent energy loss (FCEL) [13]. Results are also compared with the LHCb 𝐷 0 measurement at √ 𝑠 NN = 5.02 TeV [14].…”
Section: Pos(hardprobes2023)105mentioning
confidence: 99%
“…This is called the initial energy loss effect. In recent years, it is still an ongoing subject on both experimental and theoretical sides [24][25][26]. Therefore the initial energy loss effect is also considered.…”
Section: Introductionmentioning
confidence: 99%